Limited impact of severe drought on plant dynamics in African Savanna - Abbas, Huyam (Department of Biological Sciences, 2026)
Severe drought is defined as rainfall deficiency over an extended period of successive years. The impacts of such droughts on savanna dynamics are not well studied resulting in widely divergent views. Opportunities to study severe drought are scarce because multi-year rainfall deficits are naturally rare and occur at unpredictable intervals. South Africa experienced multi-year rainfall deficit in 2014-2016. A drought index analysis indicated that it was the worst drought in 35 years. Here we explored the response of a South African savanna ecosystem to this drought focussing on savanna tree dynamics and changes in perennial grass composition and abundance. We used open long term monitoring plots established in 2000 and distributed across broad rainfall gradients in the Hluhluwe-iMfolozi Park in KwaZulu-Natal. They are characterised by a variety of herbivore use intensity, fire frequency and soil type. We compared records of tree size and density and grass biomass and composition in 2016 (after the drought) with 2012 (before the drought). Data analysis showed a massive increase (around seven fold) in the tree population especially among the small size classes (0.1m-0.3m) in 2016 relative to 2012. Tree mortality due to drought was negligible (0.03%) and there was no substantial change in tree composition. Although grass biomass and cover decreased, drought effects on veld conditions were minor. Grass showed rapid recovery by resprouting. The decreaser species and the increaser IIb were favoured by droughts. In contrast, the increaser I species have declined while the increaser IIc species have experienced a slight decrease. In addition, drought caused a shift to palatable grazing lawn species and a decline in unpalatable grasses such as Sporobolus pyramidalis. This suggests that this South African ecosystem is resilient to severe drought. The implication is that drought might facilitate woody encroachment by reducing the competitive effect of grass and by reducing the fuel load of grass for fire.